1993
DOI: 10.1021/bi00080a027
|View full text |Cite
|
Sign up to set email alerts
|

Translesional synthesis on a DNA template containing a single stereoisomer of dG-(+)- or dG-(-)-anti-BPDE (7, 8-dihydroxy-anti-9, 10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene

Abstract: Oligodeoxynucleotides modified site-specifically with dG-(+)-trans- and dG-(+)-cis-anti-BPDE (7,8-dihydroxy-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene) or dG-(-)-trans- and dG-(-)-cis-anti-BPDE were used as templates in primer extension reactions catalyzed by the Klenow fragment of Escherichia coli DNA polymerase I. The primer could be extended past the dG-(-)-trans-BPDE adduct with small amounts of dAMP incorporated opposite the lesion. A small amount of base deletions was also observed while, with the dG-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
160
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(182 citation statements)
references
References 70 publications
19
160
3
Order By: Relevance
“…Cleavage products containing a trans-S adduct migrated slightly more slowly than did the corresponding fragments containing a trans-R adduct. Differences in electrophoretic migration for oligonucleotides containing R-versus S-BaP DE adducts have been noted previously (31,32).…”
Section: Accumulation Of Top1-mediated Dna Cleavage Complexes By Bap mentioning
confidence: 60%
“…Cleavage products containing a trans-S adduct migrated slightly more slowly than did the corresponding fragments containing a trans-R adduct. Differences in electrophoretic migration for oligonucleotides containing R-versus S-BaP DE adducts have been noted previously (31,32).…”
Section: Accumulation Of Top1-mediated Dna Cleavage Complexes By Bap mentioning
confidence: 60%
“…For example, in the case of KF Ϫ , extension beyond the lesion is more than 1 order of magnitude less efficient than insertion of any of the four dNTPs opposite the lesion site (21,27,28). Human pol , yeast pol , or the combined activities of both polymerases are not able to fully bypass any of the stereoisomeric [BP]-N 2 -dG or [BP]-N 6 -dA lesions studied and thus resemble some of the classical polymerases in terms of their lack of ability to bypass these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The stereochemistry of BPDE has an influence on its potent mutagenic and carcinogenic properties (11)(12)(13)(14). It has been shown that BPDE-adducted DNA blocks synthesis by a variety of DNA polymerases (15)(16)(17)(18)(19). Several studies have also demonstrated that BPDE adducts in DNA impede transcription (20 -27).…”
mentioning
confidence: 99%